ANALYSIS OF TRAINING AND SYSTEMS FOR FRENCH TEACHERS IN SENEGAL - LY, Thierno (International Journal of Research -GRANTHAALAYAH, 2024)
The training of future secondary school teachers of french has always played a very important role in education policy in Senegal. Indeed, among other objectives, it is essentially based on the acquisition of knowledge related to the subject of french, pedagogical and didactic skills, and a perfect knowledge of the content of secondary school curricula. This raises the issue of content and practical approaches in teacher training. Thus, the question is what curriculum content, what pedagogical and didactic tools and approaches are used to the training practices of future french teachers in Senegal. To better answer these questions, we first checked the content and arrangements for training future teachers of french. The initial results show that the content, tools and teaching approaches used in training practices are not always in line with those officially recommended and are not fully stabilised and applied in didactic situations.